PENGARUH FAKTOR DEMOGRAFI TERHADAP KEPUTUSAN PEMBELIAN MOBIL DI KOTA BANDA ACEH DENGAN PERSEPSI MEREK MEWAH SEBAGAI VARIABEL MEDIASI - Ayu Mentari, Saed Armia (Departemen Manajemen, 2016)
The study aims to examine the influence of demographic factors on purchase decisions that mediated by the perception of luxury brand. The owners and users of luxury cars in Banda Aceh is taken as a sample for this study. This study employed questionnaire as a research instrument. Purposive sampling is applied as the sampling technique. Hierarchical Linear Modelling methods of analysis are usedto determine the influence of the involved variables. The result of this study indicatesthat demographic factors have positive effect on purchase decisions and luxury brand perception have positive effect on purchase decisions. The study shows that demographic factors significantly influence the luxury brand perception or purchase decisions and also luxury brand perception significantly influence the purchase decisions. In addition, the result shows that luxury brand perception is perfectly mediated theeffect of demographic factors to purchase decisions. Keyword: Demographic Factors, Luxury Brand Perception, Purchase Decisions.